THE EPONYMOUS SITE OF THE PETREŞTI CULTURE (I).BALKAN CONNECTIONS OF SOME CERAMIC VESSELS (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2026)
The article represents a contribution with the intention to capitalise on some discoveries left, as of yet, unpublished from the important archaeological site Petreşti-Groapa Galbenă. On this occasion, three categories of artefacts are discussed, individualised by the links they reveal with the Balkan world. The first discussion concerns an early Petreşti black-topped vessel (so-called Foeni), a unique find north of the Danube, decorated on the outside with triangular impressions, and on the inside with polished motifs. In the absence of an indication of correct analogies at the time of its publication, the vessel reveals, however, good parallels with vessels from the present Greek space (Dikili Tash, Dhrepanon), as well as from Hungary. Another ceramic category in question is illustrated by several small, biconic ceramic vessels, some with torches, decorated above the shoulder with incisions in the form of semicircles. Parallels are also found in the south Danubian space (Dikili Tash), evolving in the area of Petreşti culture in painted motifs that persist until the Petreşti phase A-B. Finally, two vessels are also mentioned: a small Turdaş-type cup decorated with an incised “fir tree” and an amphora fragment with sacred signs that form a succession of two signs, repeated. These findings underscore the still unknown potential of materials from the collections of the museums in Sebeş and Alba Iulia, in relation to one of the most important Neolithic and Eneolithic sites in Transylvania.